Focal Central White Matter Lesions in Alexander Disease - Barreau, Pauline (2011)
Alexander disease is a neurodegenerative disorder of the central white matter caused by dominant mutations in GFAP, the gene encoding glial fibrillary acidic protein. Magnetic resonance imaging pattern recognition studies have established characteristic radiologic phenotypes for this disorder. In some cases, however, genetically confirmed cases do not express these features, and several reports have identified “atypical” radiologic findings in Alexander disease patients. Here, the authors report 3 genetically confirmed Alexander disease cases with focal central white matter lesions that, upon longitudinal clinical and radiologic evaluation, appear to reflect an atypical Alexander disease magnetic resonance imaging phenotype and not another pathophysiologic process such as encephalitis, infarction, or neoplasm.